The Paradox of Goodwill Measurement and the Impact of M&A Synergy Effects on Goodwill Measurement - Wei Yao; Yating Yang; Haojie Liao (Journal of Frontier in Economic and Management Research, 2025)
This study aims to elucidate the formation mechanism of the goodwill measurement paradox and assess the impact of M&A synergy effects on goodwill measurement. Drawing upon empirical evidence from case studies, such as the Geely-Volvo acquisition, and broader empirical research on listed companies, the study seeks to offer practical guidance for refining industry-specific goodwill measurement standards within the registration system. Based on the "Institutional Environment-Synergy Effect-Goodwill Measurement" analytical framework, this study selects 528 non-same-control M&A samples of A-share listed companies from 2018 to 2023 as the research objects, and uses principal component analysis and a moderated mediation model to empirically test the impact of operational, financial, and management synergy effects on goodwill measurement, as well as the moderating roles of industry heterogeneity and policy changes. The conclusions are as follows: 1. The current "difference method" in goodwill measurement shows a significant deviation, with non-synergistic premiums accounting for 21.5%, and reaching as high as 34.2% in technology-intensive industries. 2. Operational, financial, and tax synergy effects all have a positive impact on goodwill measurement, with operational synergy being the most significant (coefficient 0.315***), amplifying to 0.471*** in technology-intensive industries. Synergy effects are mainly transmitted through M&A premiums, with the mediating effect of operational synergy accounting for 42.8%. 3. After the policy strengthening in 2019, the correlation between synergy effects and goodwill measurement increased by 12.5%, but technology-intensive industries still have a high impairment rate of 15.2%, indicating that policies have yet to fully eradicate the disparities in measurement risks among industries. 4. This study is the first to quantify the moderating effects of policy changes and industry attributes on goodwill measurement, theoretically unveiling the core of the goodwill measurement paradox, and practically offering crucial guidance for refining relevant regulations, enhancing valuationtion systems, and formulating regulatory policies.